2004
DOI: 10.1097/01.brs.0000137064.85554.fa
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Whiplash-Associated Disorder From a Low-Velocity Bumper Car Collision: History, Evaluation, and Surgery

Abstract: This case of whiplash-associated disorder after a low-velocity collision highlights the difficulty in defining threshold of injury in regard to velocity. It also illustrates the value of computerized motion analysis in confirming the diagnosis of whiplash-associated disorder and in the evaluation of prognosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Permanent solutions for the chronic pain conditions of the subjects in the present study are few; one suggestion is to surgically excise or ablate symptomatic trigger points that are associated with a decrease in local and generalized pain following anesthetization. [20] Such an approach, although intriguing, requires further description and study.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent solutions for the chronic pain conditions of the subjects in the present study are few; one suggestion is to surgically excise or ablate symptomatic trigger points that are associated with a decrease in local and generalized pain following anesthetization. [20] Such an approach, although intriguing, requires further description and study.…”
Section: Discussionmentioning
confidence: 99%
“…Another 14 articles were excluded because they lacked a mention of the headache measure used or they lacked a description of the intervention. At the end of this full review (see Figure 1), 36 of the 64 articles met the final criteria [17‐52]. Two external expert reviewers were asked to review the methods and evidence tables.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical joint dysfunctions and muscle TrPs are thought, by some researchers, to be the most relevant sources of nociception in whiplashassociated disorders [36]. In a review of the whiplash literature, Fernández-de-las-Peñas et al [37] found that the most common muscles affected by TrPs are the scalenes [38], splenius capitis [39], sternocleidomastoid [40,41], upper trapezius, posterior neck muscles [42], or pectoralis minor [43]. The S-shaped cervical curvature occurring during a rear-end impact may result in a lengthening position of the sternocleidomastoid, which will result in a contraction-induced overload of this stretched muscle [44].…”
Section: Muscle Trps In Whiplash-associated Disordersmentioning
confidence: 99%